Analisa Kebijakan Peraturan Perundang-Undangan Kawasan Tanpa Rokok di Masjid Al-Ikhlas Jebres Surakarta - Noventasya Nidya Megasafitri; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Amal Insani Foundation, 2023)
Smoking is still a problem in Indonesia to fulfill the human rights of the Indonesian people in the form of a healthy and clean environment. As a form of the seriousness of the Surakarta City government to answer environmental and health problems caused by smoking, the Surakarta City government issued Regional Regulation Number 9 of 2019 concerning Smokefree Areas. The regulation states that there are 7 (seven) places that are included in the category of Non-Smoking Areas, and one of them is a place of worship. Al-Ikhlas Mosque Jebres Surakarta is one of the non-smoking areas in the form of Muslim places of worship in the city of Surakarta. The purpose of writing this article is to find out the implementation of the non-smoking area policy at the Al-Ikhlas Jebres Surakarta Mosque. The research method used is descriptive normative -doctrinal legal research. The data used are primary legal materials, and secondary legal materials using analysis techniques in the form of the syllogism deduction method. The results showed that the implementation of the no-smoking area at the Al-Ikhlas Mosque in Jebres Surakarta has not been running as it should and the local regulations regarding the No-Smoking Area have not been able to function as an instrument to minimize violations of the smoking ban at the Al-Ikhlas Mosque in Surakarta. Therefore, the results of this study will provide input to the Surakarta city government as a policy maker to improve the Surakarta City Regional Regulation Number 9 of 2019 concerning Smokefree Areas so that the regional regulation can become an instrument in minimizing violations of the smoking ban at the Al-Ikhlas Surakarta Mosque.